Kritik Asghar Ali Engineer Terhadap Teologi Islam Klasik - Mujahidin, Muhammad Saekul (Tasamuh: Jurnal Studi Islam, 2023)
The purpose of this paper is to find out Asghar Ali Engineer's thoughts on Islamic theology. This research is an analysis of the texts obtained through a qualitative study process, the primary data in this study are the writings of Asghar Ali Engineer and the secondary data in the form of writings that support Islamic theological thinking. The result of this research is Asghar Ali Engineer wants to emphasize the liberation of the oppressed who are not bound by theology and reject the existence of oppression, persecution, and human exploitation by humans. Asghar Ali Engineer wants three practical framework concepts in his liberation theology, namely: First, the concept of monotheism, which not only refers to the oneness of God, but also to the unity of mankind. Second, the concept of faith is not only interpreted as a matter of believing in God, but people who believe must be trustworthy, strive to create peace and order that are serious about creating a just and prosperous society, and believe in values. about the good in life. Third, the concept of jihad which is defined as a dynamic and consistent struggle to eliminate exploitation, corruption, and various forms of injustice